IL-10 Dampens the Th1 and Tc Activation through Modulating DC Functions in BCG Vaccination - Hui Xu; Yanjuan Jia; Yonghong Li; Chaojun Wei; Wanxia Wang; Rui Guo; Jing Jia; Yu Wu; Zhenhao Li; Zhenhong Wei; Xiaoming Qi; Yuanting Li; et al. (Mediators of Inflammation)
BCG, the only registered vaccine against Mycobacterial Tuberculosis (TB) infection, has been questioned for its protective efficacy for decades. Although lots of efforts were made to improve the BCG antigenicity, few studies were devoted to understand the role of host factors in the variability of the BCG protection. Using the IL-10KO mice and pulmonary tuberculosis infection model, we have addressed the role of IL-10 in the BCG vaccination efficacy. The data showed that IL-10-deficient dendritic cells (DCs) could promote the immune responses through upregulation of the surface costimulatory molecule expression and play an orchestra role through activating CD4+T cell. IL-10-deficient mice had higher IFN γ, TNF α, and IL-6 production after BCG vaccination, which was consistent with the higher proportion of IFN γ+CD3+, IFN γ+CD4+, and IFN γ+CD8+ T cells in the spleen. Particularly, the BCG-vaccinated IL-10KO mice showed less inflammation after TB challenge compared to WT mice, which was supported by the promoted Th1 and Tc, as well as the downregulated Treg responses in IL-10 deficiency. In a conclusion, we demonstrated the negative relationship between Th1/Tc responses with IL-10 production. IL-10 deficiency restored the type 1 immune response through DC activation, which provided better protection against TB infection. Hence, our study offers the first experimental evidence that, contrary to the modulation of BCG, host immunity plays a critical role in the BCG protective efficacy against TB.